Gedung Pertunjukan Seni Uri Sani Budaya Purbalingga dengan Pendekatan Arsitektur Jawa Kontemporer - Chundakus Habsya; Abdul Haris Setiawan; Atin N; Retno W (Universitas Muhammadiyah Palembang, 2025)
This study aims to examine land use in the public service zone, education, health, sports and recreation functions so as to obtain a suitable site and design a Performance Building and Art Gallery Building in the Purbalingga Cultural Uri Sani Complex with a Contemporary Javanese Architecture approach. The method of architectural approach is qualitative and quantitative which alternate with each other and processed into design. Data sources are informants, archives and documents. Data collection is done by interview, observation, and analysis of archives and documents. The results of the planning and design study are that the site is in a public service zone that meets broad needs, the support of environmental facilities, easy access to the site and fulfillment of the development of creativity and appreciation of the arts of the Purbalingga community and its surroundings, planning and design produce space requirements, the plan of the Performance Building and Gallery with the approach of Contemporary Javanese Architecture. The roof shape is typical of Javanese architecture, and is combined with local cultural products, namely the lawa batik art motif for the secondary skin facade and kawung batik for the decorative variety of ventilation holes. The contribution of the study is in the form of studies and design drawings of the Uri Sani Complex as a proposed design to the Purbalingga Regency Education and Culture Office and art lovers in general.